Write for your life : a guide to clear and purposeful writing (and presentations) - Wheelan, Charles J. (Tantor Media, Inc., 2022)
The bestselling author's practical guide to writing clearly and convincingly in every professional setting. Charles Wheelan has spent decades mastering effective communication skills in his work as a writer, college professor, journalist, speechwriter, political candidate, and public speaker. In Write for Your Life, he shares his best tips. He covers how to organize and present information, why it's necessary to adapt one's tone to different audiences, and when to use summaries, sidebars, bullet points, and other tools for making information more digestible. He explores the truth behind popular cliches like "Show don't tell" and "Kill your darlings," and discusses the proper use and attribution of quotations from secondary sources. Throughout, the book is leavened with memorable anecdotes from leading magazine and newspaper writers and public figures such as Winston Churchill and Elena Kagan, as well as a diverse array of the best communicators from the worlds of culture, sports, and politics. Write for Your Life is an essential guide for anyone needing to get their ideas across whether in a memo, report, presentation, fundraising letter, or speech.